2010
DOI: 10.1177/0093854809357442
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Risk Factors and Their Contributions to Existing Risk/Needs Assessment

Abstract: A growing body of scholarship faults existing risk/needs assessment models for neglecting the risk factors most relevant to women offenders. In response, a series of gender-responsive assessment models were tested for their contributions to widely used genderneutral risk needs assessments. In six of eight samples studied, subsets of the gender-responsive scales achieved statistically significant contributions to gender-neutral models. Promising results were found for the following: (a) parental stress, family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
469
4
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 371 publications
(514 citation statements)
references
References 103 publications
37
469
4
4
Order By: Relevance
“…Across all four project sites, women in prison (in Colorado, Minnesota, and Missouri), on probation (in Maui, Minnesota, and Missouri), and in prerelease settings (in Colorado and Missouri) were examined with regard to various genderneutral and "gender-responsive" (e.g., victimization, mental health problems, marginalization, relationship difficulties, and substance abuse) risk and need factors. In accordance with the NIC research objectives, the research endeavors to date have examined whether genderresponsive factors are risk factors for institutional misconduct and community recidivism, as well as whether these factors improve the classification of women when they are considered in classification assessment tools (Salisbury, Van Voorhis, & Spiropoulos, 2009;Van Voorhis et al, 2010;Wright et al, 2007). Overall, the results of these studies support the use of various gender-responsive risk factors in correctional classification systems Van Voorhis et al, 2008;Van Voorhis et al, 2010;Wright et al, 2007).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Across all four project sites, women in prison (in Colorado, Minnesota, and Missouri), on probation (in Maui, Minnesota, and Missouri), and in prerelease settings (in Colorado and Missouri) were examined with regard to various genderneutral and "gender-responsive" (e.g., victimization, mental health problems, marginalization, relationship difficulties, and substance abuse) risk and need factors. In accordance with the NIC research objectives, the research endeavors to date have examined whether genderresponsive factors are risk factors for institutional misconduct and community recidivism, as well as whether these factors improve the classification of women when they are considered in classification assessment tools (Salisbury, Van Voorhis, & Spiropoulos, 2009;Van Voorhis et al, 2010;Wright et al, 2007). Overall, the results of these studies support the use of various gender-responsive risk factors in correctional classification systems Van Voorhis et al, 2008;Van Voorhis et al, 2010;Wright et al, 2007).…”
mentioning
confidence: 85%
“…Van Voorhis and colleagues reported that relatively few women, whether they were incarcerated, on probation, or in prerelease centers, reported being married at the time of intake, although large percentages reported having at least one child under the age of 18 (Van Voorhis et al, 2010;Wright et al, 2007). Likewise, Heilbrun et al (2008) reported that women scored significantly higher on the family and marital status domain of the Level of Service Inventory than did men, indicating that this was a particularly salient area of risk for women as opposed to men.…”
Section: Women's Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…While empirical evidence suggests that adult females would benefit from a gender-specific risk assessment tool (Holtfreter & Cupp, 2007;Holtfreter & Morash, 2003;Holtfreter, Reisig, & Morash, 2004;Van Voorhis, Wright, Salisbury, & Bauman, 2010), the topic has not been as extensively studied for juveniles, and findings are mixed. Some studies have found that gender-neutral tools do not accurately predict risks for juvenile females, and suggest that they may benefit from a gender-specific risk assessment tool (Baird et al, 2013;Schmidt, Campbell & Houlding, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These needs are either "not typically seen in men, seen in men but occur at greater frequency in women, or occur in equal frequency among men and women but affect women in uniquely personal and social ways that should be reflect in current correctional assessment." (Voorhis et al 2010). In this section, each need will be identified and explained.…”
Section: Applying the Theory: Identified Gender Specific Needsmentioning
confidence: 99%